Reconstructive outcomes of Mohs surgery compared with conventional excision: A 13-month prospective study. Issue 7 (July 2015) - Wain, R.A.J.; Tehrani, H.
Summary Established in 2012, the Mersey Regional Centre for Mohs Surgery is the first UK Mohs service to be led by a Mohs trained Plastic & Reconstructive surgeon. We evaluate the resection requirements and reconstructive techniques of our patient group and compare their surgical outcome to that which would have been gained with conventional excision (CE) and reconstruction for the same lesions. 157 patients were analysed over 13 months. Had CE and reconstruction been used, 56% of patients would have received a more invasive or cosmetically less desirable reconstruction, and 24% of margins would remain incomplete. The outcome was unchanged in 20% of patients. A small but significant subgroup (9%) of patients would have lost fundamental structures e.g. orbital exenteration, or undergone reconstructions unnecessarily crossing aesthetic subunits. Whilst in its infancy, the Plastic & Reconstructive Mohs surgery service has provided a valuable contribution to the care given to patients in the Mersey and Cheshire Skin Cancer Network. Detailed referral criteria, thorough preoperative patient evaluation, and appreciation of the abilities and limits of CE have enabled the service to produce a demonstrable reconstructive benefit in 80% of patients when compared to non-Mohs resection and reconstruction.